Incidence of Respiratory Tract Infection in Children with Cyanotic and Acyanotic Congenital Heart Disease: A Comparative Study - Syafira Yasmine; I Ketut Alit Utamayasa; Bambang Herwanto (Juxta: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2022)
Highlights: 1. The incidence of respiratory tract infection (RTI) showed no difference between patients with cyanotic and acyanotic congenital heart disease (CHD). 2. RTI patients with acyanotic CHD experienced longer hospital lengths of stay.